Associations Between Postoperative Symptom Clusters and Functional Status in Lung Cancer Patients: A Cross-Sectional Study - Liu Y; Lin S; Bai M; Yi H (Cancer Management and Research)
Yali Liu,1,* Siya Lin,2,* Meirong Bai,1 Huochun Yi3 1Department of Thoracic Surgery, Zhongshan Hospital Xiamen University, School of Medicine, Xiamen University, Xiamen, Fujian, 361004, People’s Republic of China; 2School of Nursing, Fujian Medical University, Fuzhou, Fujian, 350122, People’s Republic of China; 3Center of Clinical Laboratory, Zhongshan Hospital Xiamen University, School of Medicine, Xiamen University, Xiamen, Fujian, 361004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Meirong Bai, Department of Thoracic Surgery, Zhongshan Hospital Xiamen University, School of Medicine, Xiamen University, 201 hubin South Road, Siming District, Xiamen, Fujian, 361004, People’s Republic of China, Email 157576198@qq.com Huochun Yi, Center of Clinical Laboratory, Zhongshan Hospital Xiamen University, School of Medicine, Xiamen University, 201 hubin South Road, Siming District, Xiamen, Fujian, 361004, People’s Republic of China, Email yhc1818@163.comBackground: Symptom clusters in cancer symptom management research, providing a scientific basis for developing effective strategies for symptom assessment and intervention aimed at improving patient quality of life and survival.Objective: To analyze symptom clusters in postoperative lung cancer patients, examine its influenced factor, and explore the relationship between postoperative symptom clusters and functional status in lung cancer patients.Methods: Between August 2023 and February 2024, 441 lung cancer patients who underwent surgical treatment in the Department of Thoracic Surgery at a tertiary hospital in Xiamen were selected. Data collection included a general information questionnaire, the Postoperative Patient-Reported Outcomes Scale for Early-Stage Lung Cancer Patients, the Tampa Scale for Kinesiophobia (TSK), and the Karnofsky Performance Status Scale (KPSS). Latent class analysis was employed to categorize the self-reported outcomes. Statistical analyses were performed on the relevant factors.Results: The self-reported postoperative symptoms in lung cancer patients were divided into two groups: high-symptom burden and low-symptom burden. Significant differences were observed between these groups concerning surgery duration, kinesiophobia score, personality traits, KPSS, and the use of analgesic pumps (P < 0.005). After adjusting for sex, age, lifestyle, and health status, a multi-model approach confirmed a significant inverse relationship between higher KPSS levels and higher symptom burden (P < 0.001). High-symptom levels are negatively associated with functional status (P < 0.005).Conclusion: Postoperative symptom clusters in lung cancer patients can be specifically categorized into high and low-symptom burdens. Surgery duration, kinesiophobia scores, personality traits, KPSS, and the use of analgesic pumps are significant risk factors affecting symptom burden. Postoperative symptom cluster assessment provides a scientific basis for developing effective management strategies, which may improve functional recovery and long-term outcomes in lung cancer patients.Keywords: symptom clusters, functional status, lung cancer